Efficiency of pre‐process anoxia treatment on quality of fresh‐cut pineapples cv. 'Phulae' during storage. (27th December 2021) - Supapvanich, Suriyan; Techavuthiporn, Chairat
Abstract: The aim of this study was to investigate the competency of pre‐process anoxia treatment on physicochemical quality of fresh‐cut pineapples cv. 'Phulae' during storage. The fruits were kept in anoxia atmosphere (N2 ) for 16 h before processing. The fruits were processed immediately after treatment (G1) and after storage at 13 °C for 6 days (G2). Anoxia treatment delayed the weight loss and had no effect on the L* value of both G1 and G2 fresh‐cut pineapples. The yellowness ( b* ) value of G1 fresh‐cut pineapple was maintained by anoxia. The PPO activity of anoxia‐treated G1 and G2 fresh‐cut pineapples was lower than that of untreated fresh‐cut fruits (control). Total sugars contents of both G1 and G2 anoxia‐treated fresh‐cut pineapples trended to be higher than that of control samples. Anoxia had no influence on the total ascorbic acid content during storage. The increases in total bacteria and yeast of both G1 and G2 fresh‐cut pineapples were retarded by anoxia. In conclusion, anoxia is a feasible alternative to maintaining quality and delaying microbial increases in fresh‐cut pineapples during storage. Abstract : The anoxia treatment could prevent browning and improve physicochemical quality of fresh‐cut pineapples.